Failure analysis of sandwich panels - Manmadhan Kartha Nikhil. (2009)
The aim of this research work is to determine the maximum load carrying capacity of sandwich panels with plastic skins. Two types of plastics were used for testing, acrylic and polycarbonate. The initial phase of the project consisted of modeling the sandwich panel using FEM software. And impact test model was created. Then validation of the FEM model was done by comparing the results with experimental results. The second and main stage of the project consisted of running quasistatic and impact test results on the model. Two models were used, one with acrylic skins and one with polycarbonate skins. In each model the height of the honeycomb and the plastic skin thichness was waried to study the effect on its load carrying capacity. Load-history curve were plotted for each separated case. Also load-displacement curve were also plotted for each case to study the response of the sandwich structure. Form the results of the FEM test, design graphs were modeled that shows the effect of skin thichness and core height on the load carrying capacity of the structure. It was seen that considerable improvements were shown in the maximum load carried by the structure, by increasing the skin thickness. Although increase in the maximum load carried was increased by increasing the core height, it was not significant.